2005
DOI: 10.1210/me.2004-0342
|View full text |Cite
|
Sign up to set email alerts
|

Formation of E-Cadherin-Mediated Cell-Cell Adhesion Activates Akt and Mitogen Activated Protein Kinase via Phosphatidylinositol 3 Kinase and Ligand-Independent Activation of Epidermal Growth Factor Receptor in Ovarian Cancer Cells

Abstract: E-cadherin is a well characterized adhesion molecule that plays a major role in epithelial cell adhesion. Based on findings that expression of E-cadherin is frequently lost in human epithelial cancers, it has been implicated as a tumor suppressor in carcinogenesis of most human epithelial cancers. However, in ovarian cancer development, our data from the current study showed that E-cadherin expression is uniquely elevated in 86.5% of benign, borderline, and malignant ovarian carcinomas irrespective of the degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
98
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(108 citation statements)
references
References 28 publications
7
98
1
2
Order By: Relevance
“…In accord with previous results (Sundfeldt, 2003;Reddy et al, 2005;Ahmed et al, 2007), we find that ovarian carcinomas continue to express E-cadh and we defined that E-cadh localization is maintained at cell-cell contacts during tumor progression. Furthermore, we and others have also reported that Wnt signaling is not activated in most EOCs except in the endometrioid histotype (Virnekas et al, 1994;Miotti et al, 2005).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In accord with previous results (Sundfeldt, 2003;Reddy et al, 2005;Ahmed et al, 2007), we find that ovarian carcinomas continue to express E-cadh and we defined that E-cadh localization is maintained at cell-cell contacts during tumor progression. Furthermore, we and others have also reported that Wnt signaling is not activated in most EOCs except in the endometrioid histotype (Virnekas et al, 1994;Miotti et al, 2005).…”
Section: Discussionsupporting
confidence: 93%
“…EOCs originate from the single-cell layer that covers the ovary (ovarian surface epithelium, OSE), which normally shows both epithelial and mesenchymal characteristics retaining a high degree of plasticity, expressing vimentin together with cytokeratins 8 and 18. Conversely, ovarian inclusion cysts and carcinomas have properties characteristic of Mu¨llerian epithelium, including expression of the specific epithelial marker E-cadh (Sundfeldt, 2003;Reddy et al, 2005;Ahmed et al, 2007). We demonstrated that the expression and location of E-cadh in EOC cells could be altered by the downregulated expression of caveolin-1, leading to a significant alteration in src kinase activity, and possibly contributing to the spread of EOC cells in the peritoneal cavity (Miotti et al, 2005).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Loss of E-cadherin promotes anchorage-independent growth via PI3K/Akt-mediated b-catenin/TCF signaling in human ovarian cancer cells Previous studies have indicated that E-cadherinmediated cell-cell adhesion transiently activates the PI3K/Akt signaling pathway in ovarian carcinoma cell lines (Reddy et al, 2005;De Santis et al, 2009). Thus, we next examined whether stable changes in E-cadherin expression modulate PI3K/Akt signaling by determining the phosphorylation level of Akt at Ser473.…”
Section: Resultsmentioning
confidence: 99%
“…E-cadherin is an intercellular adhesion molecule generally implicated as tumor suppressor in several types of epithelial tumors, based on findings that the expression of this homotypic adhesion molecule is frequently lost in human epithelial cancers [29][30][31]. However, it has well been shown in ovarian epithelial tumors that E-cadherin expression is much more elevated than normal ovaries, suggesting that E-cadherin can play a role in the development of ovarian carcinomas [56]. For instance, it is worth to mention that E-cadherin may serve not only as an intercellular adhesion molecule, but it may also trigger intracellular activation of proliferation and survival signals [57,35].…”
Section: Discussionmentioning
confidence: 99%